2009
DOI: 10.1128/jcm.00128-09
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Immunoblotting, Real-Time PCR, and the Goldmann-Witmer Coefficient to Diagnosis of Atypical Toxoplasmic Retinochoroiditis

Abstract: Ocular toxoplasmosis is a major cause of posterior uveitis worldwide. The diagnosis is based mainly on ophthalmological examination. Biological diagnosis is necessary in atypical cases, and this requires aqueous humor sampling by anterior chamber paracentesis. We evaluated real-time PCR targeting the Toxoplasma gondii 529-bp repeat element, the Goldmann-Witmer coefficient (GWC), and immunoblotting for the diagnosis of toxoplasmic retinochoroiditis in 54 patients with atypical uveitis. The results of these biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 18 publications
(28 reference statements)
5
70
0
3
Order By: Relevance
“…Lately, molecular methods are becoming a standard diagnostic approach in the diagnosis of ocular toxoplasmosis as well. A number of studies has already shown that a positive PCR result is not always accompanied by positive serology indicating local synthesis of IgG antibodies Talabani et al, 2009) and thus can be the only confirmation of the diagnosis (Okhravi et al, 2005).…”
Section: Aqueous Humormentioning
confidence: 99%
“…Lately, molecular methods are becoming a standard diagnostic approach in the diagnosis of ocular toxoplasmosis as well. A number of studies has already shown that a positive PCR result is not always accompanied by positive serology indicating local synthesis of IgG antibodies Talabani et al, 2009) and thus can be the only confirmation of the diagnosis (Okhravi et al, 2005).…”
Section: Aqueous Humormentioning
confidence: 99%
“…Viral retinitis and ocular tuberculosis, both of which can cause focal chorio-retinal lesions, were reported the most likely differential diagnoses for atypical OT. To accurately diagnose OT in such a situation, additional investigations would be needed (Fardeau et al 2002;Mahalakshmi et al 2006;Talabani et al 2009). These include detection of toxoplasma DNA in ocular fluids with polymerase chain reaction and intra-ocular antibody testing for the Goldman-Witmer co-efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we suspect that a large pool of OT lesions would belong to the 'atypical' category. Such lesions may be confused with other infectious and non-infectious conditions and need additional tests for accurate diagnosis, unlike the typical lesions (Fardeau et al 2002;Mahalakshmi et al 2006;Talabani et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…PCR for the detection of a Toxoplasma-specific gene region is reported to be useful [13,127]. In our previous study [13], PCR analysis using a combination of multiplex qualitative PCR and real-time quantitative PCR assays of intraocular fluids, mostly the aqueous humor, detected DNA of Toxoplasma gondii in all patients with active uveitis, but not in patients with inactive old lesions (Fig.…”
Section: Toxoplasma Gondiimentioning
confidence: 93%
“…11). In addition, to prove that the antibody production against T. gondii is taking place in the eye, it is useful to calculate the GWC [127,128]. The sensitivity of diagnosing ocular toxoplasma can be further improved by Fig.…”
Section: Toxoplasma Gondiimentioning
confidence: 99%